An Analysis Approach for Optimization Based Reconfiguration in Photovoltaic Arrays - Karakose, Mehmet; Baygin, Mehmet; Baygin, Nursena (Ieee, 2014)
Partial shading in photovoltaic (PV) arrays is an important factor that decreases the performance of the system. The reconfiguration process that uses to change of panel connections in array aims to increase of efficiency of PV array in partial shading conditions. However, optimal layout of panels with partial shading and number of switching matrixes cannot be determined exactly. In this study, an analysis approach for reconfiguration process based on optimization of panel layout and switching matrix according to partial shadings in PV array has been proposed. The reconfiguration process changes mainly connections with a switching matrix between adaptive panels and rows of fixed panels in array. Proposed approach finds continuously to energy efficiency optimal panel layout and optimal number of switching matrix according to shading conditions. Simulation results have been given to verify of proposed approach in different shading conditions and efficiency of about 15% has been obtained.
IEEE 23rd International Symposium on Industrial Electronics (ISIE) -- JUN 01-04, 2014 -- Istanbul, TURKEY
Keywords: optimization; reconfiguration; switching matrices; PV systems; partial shadings